Long-term strategies to control COVID-19 in low and middle-income countries: An options overview of community-based, non-pharmacological interventions - Chowdhury, Rajiv; Luhar, Shammi; Khan, Nusrat; Choudhury, Sohel Reza; Matin, Imran; Franco, Oscar H. (Springer Link, 2022)
This article was published in The European Journal of Epidemiology [©2020 Published by Springer, Open access, licensed under CC BY-NC-ND 4.0] and the definite version is available at: https://doi.org/10.1007/s10654-020-00660-1 The Article's website is at: https://link.springer.com/article/10.1007/s10654-020-00660-1